Rural Pandemic Preparedness: The Risk, Resilience and Response Required of Primary Healthcare - O'Sullivan B; Leader J; Couch D; Purnell J (Dove Medical Press, 2020)
Belinda O’Sullivan,1 Joelena Leader,2 Danielle Couch,3 James Purnell4 1Rural Clinical School, University of Queensland, Toowoomba, Queensland, Australia; 2Edwards School of Business, University of Saskatchewan, Saskatoon, Saskatchewan, Canada; 3School of Rural Health, Monash University, Bendigo, Victoria, Australia; 4Department of Academic Family Medicine Northern Medical Services, University of Saskatchewan, Saskatoon, Saskatchewan, CanadaCorrespondence: Belinda O’Sullivan Email belinda.osullivan@uq.edu.auAbstract: Pandemic situations present enormous risks to essential rural primary healthcare (PHC) teams and the communities they serve. Yet, the pandemic policy development for rural contexts remains poorly defined. This article draws on reflections of the rural PHC response during the COVID-19 pandemic around three elements: risk, resilience, and response. Rural communities have nuanced risks related to their mobility and interaction patterns coupled with heightened population needs, socio-economic disadvantage, and access and health service infrastructure challenges. This requires specific risk assessment and communication which addresses the local context. Pandemic resilience relies on qualified and stable PHC teams using flexible responses and resources to enable streams of pandemic-related healthcare alongside ongoing primary healthcare. This depends on problem solving within limited resources and using networks and collaborations to enable healthcare for populations spread over large geographic catchments. PHC teams must secure systems for patient retrieval and managing equipment and resources including providing for situations where supply chains may fail and staff need rest. Response consists of rural PHC teams adopting new preventative clinics, screening and ambulatory models to protect health workers from exposure whilst maximizing population screening and continuity of healthcare for vulnerable groups. Innovative models that emerge during pandemics, including telehealth clinics, may bear specific evaluation for informing ongoing rural health system capabilities and patient access. It is imperative that mainstream pandemic policies recognize the nuance of rural settings and address resourcing and support strategies to each level of rural risk, resilience, and response for a strong health system ready for surge events.Keywords: pandemic, rural primary healthcare, risk assessment, preparedness, rural system, outbreak, hazard; COVID-19